Efek Penambahan Ekstrak Jahe (Zingiber officinale Rosc.) Serta Rasio Glukosa dan Fruktosa Pada Sucrose-Free Hard Candy - Supriyanto Supriyanto; Mojiono Mojiono; Meriya Widianti Prastika Dewi (Rekayasa, 2023)
Hard candy is a non-crystalline product with a hard texture, shiny appearance and clear cooked at high temperature (140-150Â°C). One of the main ingredients in making hard candy is sucrose which can accelerate the growth of Streptococcus mutans bacteria, the main cause of dental caries. Thus, researchers conducted a study making sucrose-free hard candy ginger extract products using fructose and glucose syrup as sugar substitutes (sucrose) which are expected to inhibit the growth of Streptococcus mutans bacteria. The purpose of this study was to determine the effect of the ratio of fructose and glucose on the characteristics of sucrose-free hard candy, ginger extract (Zingiber officinale Rosc.) and find out the best formula in making sucrose-free hard candy, ginger extract (Zingiber officinale Rosc.) based on sensory tests. This research method uses Non-Factorial Complete Randomized Design (RAL). The study parameters include Ph, dissolving time, sensory, RGB color, and antibacterial. The effect of the ratio of fructose and glucose on the characteristics of sucrose-free hard candy ginger extract (Zingiber officinale Rosc.) is that the less fructose added and the more glucose, the higher the Ph of the candy, the longer the soluble time, the brighter color produced and the weaker the inhibitory power. Based on the results of sensory tests, it can be concluded that the best formulation in making sucrose-free hard candy ginger extract (Zingiber officinale Rosc.) is formula 3 with a ratio of glucose and fructose of 80:30 grams.